Application of PjBL Model by Utilizing Natural Materials Chemistry to Improve Students' 4C Skills - Harizon Harizon; Firdiawan Ekaputra (PT ARRUS Intelektual Indonesia, 2023)
The purpose of this study was to examine the effectiveness of implementing a project-based learning model by utilizing natural materials to improve students' 4C skills. 4C skills include critical thinking, communication, collaboration, and creativity skills. The sample used in this study were students who attended the R-001 class of natural material chemistry lectures in the 2023/2024 academic year of the Jambi University Chemistry Education Study Program. This research is a quasi-experimental type research with a one group pretest-posttest scheme design. Data on 4C skills were obtained using a questionnaire before and after the application of the project-based learning model by utilizing natural chemistry. Data on 4C skills were then subjected to paired samples t test. The results of the paired samples t test significance test showed a value of 0.00. These results are smaller than 0.05, so this study shows that the application of the project-based learning model by utilizing natural materials can improve students' 4C skills.